Two new species of Stenchaetothrips (Thysanoptera: Thripidae) from India - Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2008)
Two new species of Stenchaetothrips are described from India, S. hullikali and S. spinulae. The former was collected from rice seedlings in Karnataka, and the latter from bamboo vegetation in Delhi State. S. spinulae shows sexual dimorphism in colour, with the females brown but the males bicoloured. S. hullikali has ocellar seta pair III sub-equal to pair II.